Identification and molecular detection of Arbuscular Mycorrhizal Fungi colonized naturally in citrus roots in nurseries - YENNY SARIASIH; SITI SUBANDIYAH; SRI WIDYANINGSIH; TAHIR KHURSHID; JIANHUA MO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Sariasih Y, Subandiyah S, Widyaningsih S, Khurshid T, Mo J. 2023. Identification and molecular detection of Arbuscular Mycorrhizal Fungi colonized naturally in citrus roots in nurseries. Biodiversitas 24: 6283-6290. Citrus plants heavily depend on arbuscular mycorrhizal (AMF), a diverse collection of fungi. The objective of this study was to investigate the root colonization, spore density, spore morphology, and molecular identification of AMF colonizing four citrus root species: Japansche Citroen (Citrus limonia Osbeck.), Cleopatra mandarin (Citrus reshni), Salam (Fortunella japonica cv. "Salam"), and Rough Lemon (Citrus jambhiri). AMF was identified by observing spore morphology and molecular PCR methods using the group-specific primers of Glomeromycota, AML1/AML2. Based on the morphological observation, C. limonia was found with the highest root colonization (50%), followed by F. japonica cv Salam (44%), C. reshni (38%), and C. jambhiri (36%). The highest number of AMF spores was found on C. jambhiri rhizosphere soil, which had 1,379 spores/100 g of soil with the lowest percentage of root colonization. Three mycorrhizal genera were identified, with Funneliformis (syn. Glomus) being the most dominant genus, followed by Gigaspora and Acaulospora. The sequence of PCR products confirmed the highest similarity range from 83.7-99.0% to that of Funneliformis, followed by Acaulospora at a similarity range from 83.3-99.0% and found on all of the citrus species. The similarity sequence of the PCR products to that of Gigaspora ranged between 83.3-95.0%, which was only found on C. reshni and C. jambhiri.